Optimized Synthesis Temperature and Time to Obtain Crystalline Carbon Nitride with Enhanced Photocatalytic Activity for Phenol Degradation - Leny Yuliati; Mohd Hayrie Mohd Hatta; Siew Ling Lee; Hendrik Oktendy Lintang (Indonesian Journal of Chemistry, 2020)
In this work, the crystalline carbon nitride photocatalysts were synthesized by an ionothermal technique with varied synthesis temperature of 500, 550, and 600 °C, and synthesis time of 2, 4, and 6 h. Fourier transform infrared spectra showed the successful formation of the prepared carbon nitrides from their characteristic vibration peaks. X-ray diffraction patterns suggested that the same phase of poly(triazine imide) and heptazine could be observed, but with different crystallinity. The optical properties showed that different temperatures and synthesis time resulted in the different band gap energy (2.72–3.02 eV) as well as the specific surface area (24–73 m2 g–1). The transmission electron microscopy image revealed that the crystalline carbon nitride has a near-hexagonal prismatic crystallite size of about 50 nm. Analysis by high-performance liquid chromatography showed that the best photocatalytic activity for phenol degradation under solar light simulator was obtained on the crystalline carbon nitride prepared at the 550 °C for 4 h, which would be due to the high crystallinity, suitable low band gap energy (2.82 eV), and large specific surface area (73 m2 g–1). Controlling both the temperature and synthesis time is shown to be important to obtain the best physicochemical properties leading to high activity.